2022
DOI: 10.3390/ijms23073913
|View full text |Cite
|
Sign up to set email alerts
|

LPS Response Is Impaired by Urban Fine Particulate Matter

Abstract: Fine particulate matter (PM2.5) is a complex mixture of components with diverse chemical and physical characteristics associated with increased respiratory and cardiovascular diseases mortality. Our study aimed to investigate the effects of exposure to concentrated PM2.5 on LPS-induced lung injury onset. BALB/c male mice were exposed to either filtered air or ambient fine PM2.5 in an ambient particle concentrator for 5 weeks. Then, an acute lung injury was induced with nebulized LPS. The animals were euthanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Moreover, these data would suggest that the contemporary PM2.5 sample from Chiang Mai is less immunostimulatory than the historic SRM 1648a. Our study suggests that preexposure to PM alters the response of human neutrophils stimulated by LPS, consistent with findings in a recent study using a mouse model 38 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, these data would suggest that the contemporary PM2.5 sample from Chiang Mai is less immunostimulatory than the historic SRM 1648a. Our study suggests that preexposure to PM alters the response of human neutrophils stimulated by LPS, consistent with findings in a recent study using a mouse model 38 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that PM increased IL-8, but reduced IL-8 receptor expression and migration in response to LPS stimulation. This is relevant to a previous study in a mouse model in which PM reduced neutrophil migration to the lungs in response to LPS by decreasing gene expression of TLR-4 and MyD88 38 . Moreover, TLR4-induced loss of IL-8 receptor (CXCR2) was modified by enhanced LPS presentation efficiency 43 .…”
Section: Discussionmentioning
confidence: 52%